Multiple Linear Regression Analysis on Corporate Governance Mechanisms for Banking Financial Performance - siti umyana; Bambang Haryadi (International Journal of Science, Engineering, and Information Technology, 2021)
Banking every year has progressed quite rapidly to compete in the financial field, by offering lower interest rates and some tips that attract the attention of banking consumers are enough to attract people to use the bank's financial services. However, it should also be noted that every bank, be it or general, has various strategies to attract the attention of customers who will use the bank's services, to make customers more comfortable and interested in using the services of a bank, there are several mechanisms that are applied, and in this study researchers used the variable of the corporate governance mechanism as an independent variable and the financial performance variable as a dependent variable. By using the method of quantitative descriptive approach by taking data from several banks. So the researchers got the results that were thrown on a Likert scale. From the results of research processed using the help of several SPSS V.21 applications, it shows that directors and institutional ownership have a good impact on the organizational performance of a bank. However, the ownership of management, independent boards, and audit committees does not have a good impact on the financial performance of banks.